Animation Between Magic, Miracles and Mechanics: Principles of Life in Medieval Imagery, by Hans Henrik Lohfert Jørgensen, Laura Katrine Skinnebach, and Henning Laugerud (eds.) - Cusack, Carole M. (International journal for the study of new religions, 2023)
Animation Between Magic, Miracles and Mechanics: Principles of Life in Medieval Imagery, by Hans Henrik Lohfert Jørgensen, Laura Katrine Skinnebach, and Henning Laugerud (eds.). Aarhus: Aarhus University Press, 2023. Hb. 295 pp. US$94.68. ISBN: 9788772196534